2016
DOI: 10.1007/s10549-016-4065-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of exercise intervention in breast cancer patients: is mobile health (mHealth) with pedometer more effective than conventional program using brochure?

Abstract: Overall, both the mHealth coupled with pedometer and conventional exercise education using a brochure were effective in improving physical function, physical activity, and QOL. This study provides a basis of mHealth research in breast cancer patients for progressing further developing field, although superiority of the mHealth over the conventional program was not definitely evident.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
354
2
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 170 publications
(360 citation statements)
references
References 23 publications
1
354
2
3
Order By: Relevance
“…The included studies involved 2734 participants from different populations. Twelve studies included healthy adults, also including inactive and/or overweight [35, 36, 3842, 44, 4749, 52], whereas four studies were conducted in patients with (chronic) diseases [37, 43, 50, 51], one study in participants with an elevated risk of cardiovascular disease [45] and another study included stroke survivors [46]. In all studies, except one, physical activity was promoted through a smartphone or tablet application.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The included studies involved 2734 participants from different populations. Twelve studies included healthy adults, also including inactive and/or overweight [35, 36, 3842, 44, 4749, 52], whereas four studies were conducted in patients with (chronic) diseases [37, 43, 50, 51], one study in participants with an elevated risk of cardiovascular disease [45] and another study included stroke survivors [46]. In all studies, except one, physical activity was promoted through a smartphone or tablet application.…”
Section: Resultsmentioning
confidence: 99%
“…In all studies, except one, physical activity was promoted through a smartphone or tablet application. The application was, in most studies, supported by a pedometer [3639, 50, 52] or accelerometer [4042, 4447, 49, 51]. In the other study, physical activity was promoted by an accelerometer which could be synchronized with an online dashboard [43].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have also shown that mobile health apps can assist with medication management and provide reminders for doctor appointments with resulting improvement in self-care behavior, quality of life, and healthcare utilization [11]. In the cancer setting, mobile health apps have been designed for various uses which include providing education and support, monitoring symptoms and facilitating symptom reporting, monitoring medication adherence, promoting physical activity, and monitoring nutritional status and surgical care [12][13][14][15][16][17][18][19][20]. However, very few mobile apps have been tailored specifically for older adults with cancer who have complex healthcare needs, and/or for their caregivers who themselves frequently have health care issues [21].…”
Section: Scope Of the Problemmentioning
confidence: 99%
“…Another study including 303 women with cancer reported a reduction in insomnia, an increase in levels of vigorous physical activity and stretching after a six-week web health program [34]. The positive effects of a mobile health and pedometer on physical fitness, physical activity and quality of life of patients with breast cancer have been recently described [35]. The emerging field of mobile health offers the potential to assess the effects of a lifestyle intervention delivered by a web and/or a mobile application in breast cancer patients.…”
Section: Introductionmentioning
confidence: 98%